Sedimentary Anthropogenic Carbon Signals From the Western Pacific Margin for the Last Century - Lee, Jay; Yang, Rick J.; Lin, Hui-Ling; Chen, Yi-Chi; Cai-Li, Ren-Yi; Ren, Haojia; Liu, James T. (Frontiers in Earth Science, 2022)
The declining trend of the δ13C of tropical corals over the last century was about −0.01‰ year−1, according to global coral records. The decrease was attributable to the significant input of anthropogenic CO2 (13C Suess effect) to the atmosphere. Previous studies of δ13C in corals suggested that the signal of the anthropogenic carbon in the Pacific and Indian Oceans were weaker than that in the Atlantic Ocean. However, biases relating to environments in which corals grew caused concerns. To investigate the anthropogenic carbon signal in the Western Pacific, foraminiferal records in a suite of 13 box cores with good age control were obtained from the continental slope off southwestern Taiwan between 2004 and 2006. δ18O values of planktonic foraminifera (Globigerinoides sacculifer or so-called Trilobatus sacculifer) in collected cores were relatively stable at −2.5‰ to −2‰ in the last century, but foraminiferal δ13C had a gradual secular decline after the 1900s. The decline trend of δ13C began to intensify after the 1960s, and its rate was similar to that observed in the Atlantic. Similar decline trends of δ13C were also found in coral records at regions where the human activity is high (Liuqiu) and low (Dongsha). Our findings indicate that the anthropogenic carbon signal in the Western Pacific was not weaker than that recorded in the Atlantic, and the nearshore sediment can supplement the lack of δ13C records in corals, which are deficient when the environment is not suitable to grow.